Impacts of hypoxia on the mesozooplankton community structure in a semi-enclosed bay - Lee, Eun Hye; Choi, Seo Yeol; Seo, Min Ho; Soh, Ho Young (Frontiers in Marine Science, 2022)
Gamak Bay is frequently affected by hypoxia in summer. Therefore, this study aimed to examine the effect of hypoxia on the mesozooplankton community of this region. Mesozooplankton samples were obtained biweekly (28 times) at a hypoxic station (inner bay) and a normoxic station (middle bay) using a conical net (mesh size 200 μm; mouth diameter 30 cm) from April 2020 to April 2021. In the inner bay, hypoxia was observed a total of five times between early June and late September, whereas no instances of hypoxia were detected in the middle bay. During the hypoxic period, mesozooplankton abundance was higher in the inner bay than the middle bay (p < 0.05). During the normoxic period, there was no difference between the inner bay and the middle bay (p > 0.05). The dominant species in the hypoxic period were three species of cladocerans (Pleopis polyphemoides, Pseudoevadne tergestina, Penilia avirostris) and the copepod Acartia sinjiensis. The abundance of cladocerans was higher in the inner bay, and that of A. sinjiensis was higher in the middle bay (p < 0.05). In addition to water temperature, salinity, and size-fractionated Chl-a concentration, mesozooplankton abundance was also significantly correlated with the bottom DO concentration. Collectively, our findings suggest that hypoxia can affect mesozooplankton abundance and occurrence times.